SCIENTIFIC APPROACHES TO THE MANAGEMENT OF TEACHING STAFF OF SECONDARY SCHOOLS IN EDUCATIONAL MANAGEMENT - Muzaffar Ummatovich Kurbanov (Galaxy International Interdisciplinary Research Journal, 2023)
At the end of the 19th-beginning of the 20th centuries, industry entered the era of mass production, and the tasks of managing enterprises were sharply complicated. Old methods of management began to feel increasingly inefficient. The realization of an objective need for new forms and methods of management led to the emergence of management. From the very beginning, management sought to answer one main question. “How to organize management effectively?” His entire evolution was because answers to this question were offered. They were subjected to practical tests, criticized, supplemented or rejected, and new solutions were developed based on radically different foundations.